Expanded food choice as a possible factor in the evolution of sociality of Vespidae (Hymenoptera) - Da Silva, Eliani Rodrigues [UNESP]; Jaffe, Klaus [UNESP] (My University, 2002)
A recent theory suggests that economic considerations are more important than genetic ones in the emergence and maintenance of social behavior. Evolution of social behavior in wasps, thus, could be based on the development of worker castes, which increase the efficiency of brood care and energy use of the colony. If so, social wasps should collect a larger range of prey, favoring polyethism, as social behavior should increase the adaptive value of social species among wasps by increasing the range of prey accessible. We explored the literature and showed that the Eumeninae, which are mostly solitary, draw prey from significantly fewer orders of arthropods than wasps in the subfamily Vespinae and Polistinae, which are mainly social, supporting the hypothesis that social behavior may have emerged as a more efficient way to feed and care for the young by opening a wider range of food sources, increasing the amount of food and quality of care provided to the young. Two alternative explanations of this data are also discussed.
Keywords: Economic efficiency; Evolution; Generalist and specialists; Prey; Social behavior; Arthropoda; Eumeninae; Hymenoptera; Polistinae; Vespidae; Vespinae